(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2013)
Education is a powerful and pervasive agent for all rounddevelopment, individual and social transformation. This alone can sustainculture and civilization. Education should lead to the development ofintegrated personality and inculcate values like patriotism. Spirit of nationalunity and a healthy appreciation of the rich variety of cultural expressionsand promote a humanistic outlook. Value education is a many-sided endeavor as value itself.The theory and practice of value education speak to emotional, rational andactive selves of individuals. It helps individuals to resolve or accept conflictswith others and to realize their beliefs in action. The school authorities canorganize various activities and functions for the purpose of inculcation ofvalues in the students. This paper talks about the importance which is beinggiven to the concept of value education along with the academic andprofessional education to the students so they can empathise with the societyto which they are going to belong and contribute to the growth and developmentof the world in a big way.